The Many Faces of Slavery New Perspectives on Slave Ownership and Experiences in the Americas - Aje, Lawrence; Armstrong, Catherine (Bloomsbury Academic, 2019)
While the plantation accounts for 90% of slave ownership and experience in the Americas, its centrality to the common conceptions of slavery has arguably led to an oversimplified understanding of its multifarious forms and complex dynamics in the region. Published open access, The Many Faces of Slavery explores non-traditional forms of slavery that existed outside the plantation system to illustrate the pluralities of slave ownership and experiences in the Americas, from the 17th to the 19th century. Through a wide range of innovative and multi-disciplined approaches, the book's chapters explore the existence of urban slavery, slave self-hiring, quasi-free or nominal slaves, domestic slave concubines, slave vendors, slave soldiers and sailors, slave preachers, slave overseers, and many other types of "societies with slaves." Moreover, it documents unconventional forms of slave ownership like slave-holding by poor whites, women, free blacks, Native Americans, Jewish Americans, corporations and the state. The Many Faces of Slavery broadens our traditional conception of slavery by complicating our understanding of slave experience and ownership in slavery-practising societies throughout Atlantic history. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Knowledge Unlatched.